Analysis of Sedimentation in Wonogiri Reservoir - Tri Joko Inti Budi Santosa (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2016)
The Wonogiri reservoir which has 730 million cubic meters of total storage, 90 square kilometers of water area, and 1260 square kilometers of catchment area, is located in the Wonogiri Regency, Central Java Province. It was first established in 1981 and began its operation in 1982 with the expectation that it would last for about 100 years. Today (2002) the reservoir has got a serious problem of sedimentation. The sedimentation is so large that it would decrease the capacity storage of the reservoir and would shorten the length of operation. Therefore, it is necessary to predict the sediment that comes into the reservoir. This research would be based on the total sediment calculation of the sedimentation, through some methods, such as echo sounding measured data, land erosion (USLE), the calculation of the sediment in rivers. This research calculates the sediment capacities based on the water flow data and the sediment rating curves in rivers of Keduang, Tirtomoyo, Temon, upstream reach of Bengawan Solo, Alang, and Wuryantoro. The suspended load was calculated based on the sediment rating curves, whereas the bed load was computed as the percentage of the suspended load. The sum of both calculation results would be the total sediment. The calculation result showed that the total sediment which has come into the reservoir is 6.68 million cubic meters per year. As a comparison, the writer noted that the former researcher using echo sounding method done by the Faculty of Geography of the Universitas Gadjah Mada in 1985, it found that the total sediment capacity which came into the reservoir was 6.60 million cubic meters per year or 5.40 mm per year of sheet erosion. The other research using echo sounding method done by JICA in 2000 found that the total sediment which had come into the reservoir was 4.50 million cubic meters per year or 3.50 mm per year of sheet erosion. By knowing the results of calculation of the total sediment, we can learn that different methods provide different results and it is still uncertain which one is true.